Proper development of long-lived memory CD4 T cells requires HLA-DO function - Song, Nianbin; Welsh, Robin A.; Sadegh-Nasseri, Scheherazade (Frontiers in Immunology, 2023)
Introduction HLA-DO (DO) is an accessory protein that binds DM for trafficking to MIIC and has peptide editing functions. DO is mainly expressed in thymic medulla and B cells. Using biochemical experiments, our lab has discovered that DO has differential effects on editing peptides of different sequences: DO increases binding of DM-resistant peptides and reduces the binding of DM-sensitive peptides to the HLA-DR1 molecules. In a separate line of work, we have established that appropriate densities of antigen presentation by B cells during the contraction phase of an infection, induces quiescence in antigen experienced CD4 T cells, as they differentiate into memory T cells. This quiescence phenotype helps memory CD4 T cell survival and promotes effective memory responses to secondary Ag challenge. Methods Based on our mechanistic understanding of DO function, it would be expected that if the immunodominant epitope of antigen is DM-resistant, presentation of decreased densities of pMHCII by B cells would lead to faulty development of memory CD4 T cells in the absence of DO. We explored the effects of DO on development of memory CD4 T cells and B cells utilizing two model antigens, H5N1-Flu Ag bearing DM-resistant, and OVA protein, which has a DM-sensitive immunodominant epitope and four mouse strains including two DO-deficient Tg mice. Using Tetramers and multiple antibodies against markers of memory CD4 T cells and B cells, we tracked memory development. Results We found that immunized DR1+DO-KO mice had fewer CD4 memory T cells and memory B cells as compared to the DR1+DO-WT counterpart and had compromised recall responses. Conversely, OVA specific memory responses elicited in HA immunized DR1+DO-KO mice were normal. Conclusion These results demonstrate that in the absence of DO, the presentation of cognate foreign antigens in the DO-KO mice is altered and can impact the proper development of memory cells. These findings provide new insights on vaccination design leading to better immune memory responses.